Asymmetric Organocatalysis and Photoredox Catalysis for the α‐Functionalization of Tetrahydroisoquinolines. Issue 10 (14th March 2018) - Hou, Hong; Zhu, Shaoqun; Atodiresei, Iuliana; Rueping, Magnus
Abstract : The asymmetric α‐alkylation of tetrahydroisoquinolines with cyclic ketones has been accomplished in the presence of a combined catalytic system consisting of a visible‐light photoredox catalyst and a chiral primary amine organocatalyst. The desired products were obtained in good yields, high enantioselectivity, and good to excellent diastereoselectivity. (PC: photoredox cycle, EN: enamine cycle). Abstract : A combined photoredox/organocatalytic system for the asymmetric α‐alkylation of tetrahydroisoquinolines (THIQs) has been developed. In this protocol, a chiral organocatalyst enables a high level of enantio‐ and diastereocontrol for the oxidative coupling reaction of THIQs with simple cyclic ketones.